Undergraduate attitudes and expectations of mobile banking - Hanudin Amin; Hamid Rizal; Geoffrey Harvey Tanakinjal; Suddin Lada (Array Development, 2006)
This study analyzed the undergraduate students' willingness on adopting the usage of mobile phone in banking transaction' focusing on Islamic banking in FT, Labuan. Research has been conducted to analyze the students' attitudes and expectations toward mobile banking. Furthermore, students' socio-demographic elements were also studied and analyzes in relations with the study. As noted, sample was taken from students of Universiti Malaysia Sabah, Labuan International Campus. A total of 615 students were approached using convenience sampling modes. And, the finding illustrate that students tend to learn and adopt mobile banking in their banking transactions. In addition, the results also demonstrate students' attitudes and expectations to be the most consistent explanatory factors in predicting their willingness on adopting mobile banking usage in the future. In the nutshell, the findings were in-line with the previous study conducted by Howcroft, Hamilton and Hewer (2002), Sivanand, Geeta and Suleep (2004) and Laforet and Li (2005).